Proses berpikir kreatif siswa dalam menyelesaikan soal kontekstual pada materi perbandingan berdasarkan teori Wallas - Zaiturrahmah, Zaiturrahmah; Mirza, Ade; Siregar, Nurfadilah; Sugiatno, Sugiatno; Rustam, Rustam (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This study aims to determine and describe the creative thinking process skills of SMP Negeri 2 Sungai Ambawang students in solving contextual problems related to the topic of ratios based on Wallas' theory. The research method used is descriptive method with a qualitative approach. The research instruments used were creative thinking tests and interview guidelines. The data sources used were the answers to students' creative thinking tests and the results of interviews with students by researchers. This study reveals about students' creative thinking processes with three criteria for thinking levels, namely students with high, medium and low abilities. Of the 22 students, 23% were at a high creative thinking level, 32% were at a moderate creative thinking level and 45% were at a low creative thinking level. Students who are at a high level of creative thinking are able to go through all stages of creative thinking based on Wallas, at an intermediate level they are able to go through the Wallas creative thinking stage but are constrained in verification and do not find more than one way of solving it, while students at a low level do not go through the preparation stage and verification but find creative ways to solve problems.